Relationship Between Health-related Behavioral and Psychological Factors and Cardiovascular and Cerebrovascular Diseases Comorbidity Among Korean Adults With Diabetes - Eun Sun So, PhD; Young Ran Chin, PhD; In Sook Lee, PhD (Asian Nursing Research, 2011)
Purpose: This study aims to explore the relationships between health-related behavioral and psychological factors and cardiovascular and cerebrovascular diseases (CCVD) comorbidities among Korean adults with diabetes mellitus (DM). Methods: Data included in the Fourth Korean National Health and Nutrition Examination Survey were used. This study compared three groups: those diagnosed with DM only, DM and hypertension, DM, hypertension and CCVD using multinomial logistic regression analyses and the classification and regression tree (CART) model. Results: Weight control (OR = 4.01) and depression (OR = 2.37) are related with increased odds of having hypertension and CCVD comorbidity in those with DM. The CART model suggested that the high prevalence risk groups for hypertension or CCVD comorbidities were diabetic adults aged between 51 and 69 with a body mass index of 25 and above and those aged 70 and above. Conclusion: For effective control of CCVD comorbidities among diabetic Korean adults, psychological support for depression and weight control need to be prioritized when managing DM. Weight control intervention needs to be reinforced for DM patients aged between 51 and 69 and that even if BMI is below 25, the occurrence of comorbidities needs to be carefully monitored for DM patients aged 70 or older.